Málaga, Spanien. Los Castillejos de Alcorrín – eine befestigte Siedlung in phönizischer Einflusssphäre an der Meerenge von Gibraltar. Die Arbeiten der Jahre 2016 und 2017 - Marzoli, Dirce (e-Forschungsberichte des DAI, 2017)
Los Castillejos de Alcorrín is situated between the Strait of Gibraltar and the Tartessian hinterland. The Phoenician fortress was built in the late 9th century BD and used for only about 100 years. The research at Alcorrín is part of a larger project on Phoenician Archaeology of DAI Madrid in cooperation with partners and institutions in Spain and Germany. A part of this project deals with the early contacts between the Phoenician and indigenous population at geographically distinctive places in the West of the oikumene. During the campaign of 2016 a rectangular house, severely damaged by erosion, was unearthed in the eastern part of the acropole. Its ceramic findings consist almost exclusively of handmade vessels of indigenous origin. The trench next to the house delivered among other things hints of metallurgical activities and a pit which was used for cultic purposes.